The bible speaks today : The message of Luke : the saviour of the world - Wilcock, Michael (Leicester IVP, 1979)
"Luke the physician was fascinated by people--rich and poor, Jews and Gentiles, men and women, rulers and slaves. In his Gospel he delights to portray Jesus as the Saviour not of an elite group but of anyone, in any condition, who turns to him. Jesus is indeed the Saviour of the world. Luke knew exactly what he was doing when he wrote his Gospel. He tells us his goal in the opening verses: to set forth an orderly and accurate account of what had been accomplished by the life and teaching of Jesus Christ. In this up-to-date exposition, Michael Wilcock gives special attention to these opening words. Then, as he examines the individual deeds and sayings of Jesus, he shows how the structure of Luke's narrative brings out their meaning. The good news of Luke is still true today. No one is beyond redemption unless he chooses to put himself there. This message has implications not only for our personal lives but for our churches and for society as a whole"--Page 4 of cover.
Luke introduces the Gospel (1:1-4) -- 'His people's hope' (1:5-80) -- The child of good omen (2:1-52) -- The Son of God (3:1 -- 4:30) -- 'His word was with authority' (4:31 -- 5:39) -- Israel reborn (6:1-49) -- Good news (7:1 -- 8:21) -- Lord of the new Israel (8:22-56) -- Mission of the new Israel (9:1-50) -- The way (9:51 -- 10:42) -- The gift of the Spirit (11:1 -- 12:12) -- 'When he comes' (12:13 -- 13:21) -- The narrow door (13:22 -- 14:35) -- Joy in heaven (15:1-32) -- The challenge (16:1 -- 18:14) -- Royal progress (18:15 -- 19:44) -- The temple (19:45 -- 21:38) -- Satan's hour (22:1 -- 23:25) -- The cross (23:26-56) -- The first day of the week (24:1-53).
Originally published: 1979, under title: Saviour of the world : the message of Luke's gospel. Also published under title: Savior of the world : the message of Luke's gospel.
Includes bibliographical references.
Keywords: Bible. -- Commentaries; Bible -- N.T -- Luke - Expositions